Modelling the Relationship Between Information Technology Infrastructure and Organizational Agility: A Study in the Context of India. Issue 2 (April 2018) - Panda, Sukanya; Rath, Santanu Kumar
This article mainly investigates the impact of information technology (IT) infrastructure on organizational agility. Primary data collected from 300 business and IT executives working in various publicly owned banking groups functioning across India have been used for this study and a structural equation modelling (SEM) is employed to assess the IT-agility link. This article reports two-folded research findings. First, IT infrastructure enables both the sensing and responding components of organizational agility. Second, firms should not overlook the IT-agility contradiction, that is, the impeding role of IT towards achieving augmented agility. This study greatly contributes to the information systems (IS) literature as it has meticulously explored the much discussed but understudied human IT-agility linkage. The present research has successfully established the significant positive relationship between the critical dimensions of agile human IT infrastructure, namely, business functions, interpersonal management, technology management expertise and organizational sensing and responding agilities.